2020
DOI: 10.1126/sciadv.abb9605
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM and MD infer water-mediated proton transport and autoinhibition mechanisms of V o complex

Abstract: Rotary vacuolar adenosine triphosphatases (V-ATPases) drive transmembrane proton transport through a Vo proton channel subcomplex. Despite recent high-resolution structures of several rotary ATPases, the dynamic mechanism of proton pumping remains elusive. Here, we determined a 2.7-Å cryo–electron microscopy (cryo-EM) structure of yeast Vo proton channel in nanodisc that reveals the location of ordered water molecules along the proton path, details of specific protein-lipid interactions, and the architecture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 68 publications
(94 reference statements)
10
59
0
Order By: Relevance
“…Recently, the remarkable studies showed the glycolipid dolichol phosphate-linked glycan (Dolichol-p-p-Glycan) can bind to the C-terminal domain (CTD) of subunit a partially mediating the interaction between the subunit a and c-ring 12,30 . Although our previous map could not identify this molecule 11 , the current map reveals the morphology of this glycolipid unambiguously supporting the previous structural and mass spectrometry identifications 12,30 ; therefore, we have built it into the model (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the remarkable studies showed the glycolipid dolichol phosphate-linked glycan (Dolichol-p-p-Glycan) can bind to the C-terminal domain (CTD) of subunit a partially mediating the interaction between the subunit a and c-ring 12,30 . Although our previous map could not identify this molecule 11 , the current map reveals the morphology of this glycolipid unambiguously supporting the previous structural and mass spectrometry identifications 12,30 ; therefore, we have built it into the model (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Since the Dolichol-p-p-Glycan were found in the cryo-EM maps of yeast, rat, bovine, and human V-ATPase 10,12,30,31 , it suggests that the Dolichol-p-p-Glycan may play an important role in facilitating the proton translocation and/or the assembly of V o domain. The specific function of Dolichol-p-p-Glycan in V-ATPase need to be further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…6 d ). Up to now, the largest transmembrane domains embedded in MSP-based NDs are those of the yeast vacuolar ATPase V o proton channel (Roh et al ., 2018, 2020) and of the human calcium homeostasis modulator 5 (CALHM5) (Liu et al ., 2020), which comprise 48 and 44 transmembrane α -helices, respectively. Despite a lower number of transmembrane α -helices, the diameter of CALHM5 is wider than that of ATPase V o due to the presence of a large 60 Å diameter pore at the center.…”
Section: An Overview Of Surfactant Usage At the Vitrification Stepmentioning
confidence: 99%
“…In this structure three molecules of MSP1E3D1 scaffold stabilize the protein complex by forming rings of different diameter around middle transmembrane part and around c‐ring. Reproduced with permission from Roh et al 114 Open access article published under the CC BY license…”
Section: Introductionmentioning
confidence: 99%
“…Very recently a collaboration from several laboratories demonstrated that long chain lipids and expanded hydrophobic surface of Vo‐channel of vacuolar ATPase could assemble with three MSP1E3D1 scaffold proteins and revealed the structure of the resulting nanodisc by Cryo‐EM (Figure 3c). 114 This work provided the membrane environment necessary to reveal the detailed mechanism of proton translocation by the vacuolar ATPase and a high resolution structure of both the proton channel and scaffold protein.…”
Section: Introductionmentioning
confidence: 99%